2017
DOI: 10.1128/mbio.00944-17
|View full text |Cite
|
Sign up to set email alerts
|

AIM2-Like Receptors Positively and Negatively Regulate the Interferon Response Induced by Cytosolic DNA

Abstract: Cytosolic DNAs derived from retrotransposons serve as pathogen-associated molecular patterns for pattern recognition receptors (PRRs) that stimulate the induction of interferons (IFNs) and other cytokines, leading to autoimmune disease. Cyclic GMP-AMP synthase is one PRR that senses retrotransposon DNA, activating type I IFN responses through the stimulator of IFN genes (STING). Absent in melanoma 2 (AIM2)-like receptors (ALRs) have also been implicated in these pathways. Here we show that the mouse ALR IFI205… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 65 publications
2
63
0
1
Order By: Relevance
“…In MEFs derived from TREX1knockout (KO) mice, interferon induction is dependent on cGAS (11,12), a recently discovered principal sensor of cytosolic DNA (13). Furthermore, Nakaya et al (14) reported that the Aim2 like receptors (ALRs) Aim2 and Ifi205 participated in both positive and negative regulation of the IFN/cytokine response to mouse retroelement DNAs that accumulated in TREX-deficient cells. Human loss-of-function mutations in TREX1 can cause autoimmune and autoinflammatory disorders, including Aicardi-Goutieres syndrome (AGS), which has features that mimic congenital viral infection and systemic lupus erythematosus (SLE) (12,15,16).…”
mentioning
confidence: 99%
“…In MEFs derived from TREX1knockout (KO) mice, interferon induction is dependent on cGAS (11,12), a recently discovered principal sensor of cytosolic DNA (13). Furthermore, Nakaya et al (14) reported that the Aim2 like receptors (ALRs) Aim2 and Ifi205 participated in both positive and negative regulation of the IFN/cytokine response to mouse retroelement DNAs that accumulated in TREX-deficient cells. Human loss-of-function mutations in TREX1 can cause autoimmune and autoinflammatory disorders, including Aicardi-Goutieres syndrome (AGS), which has features that mimic congenital viral infection and systemic lupus erythematosus (SLE) (12,15,16).…”
mentioning
confidence: 99%
“…The phenotype of mice deficient of all 13 AIM2‐like PYHIN proteins indicated that p202 might not be absolutely required for DNA‐induced type I IFN production . However, currently we could not exclude the possibility that the lack of influence on DNA‐induced IFN expression in these mutant mice might be attributed to simultaneous deletion of multiple positive and negative regulators . In addition to AIM2 and IFI16‐α, whether IFI16‐β might interact with other human PYHIN proteins IFIX and MNDA to modulate their activity merits further analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Our data are consistent with a requirement for both DDX41 and cGAS, the former perhaps in complex with IFI203, to achieve the full antiviral IFN response to retroviral reverse transcripts not protected by capsid or blocked by APOBEC3 proteins. Whether DDX41 requires interaction with IFI203 to achieve maximum effect in vivo will also be important to determine; however, Ifi203 shares a high degree of identity in the noncoding as well as coding regions with several other genes in the ALR locus, making a gene-specific knockout difficult to achieve (51). How nucleic acid-bound DDX41 activates STING is also not yet understood, although the two molecules are known to directly bind each other (9, 13)…”
Section: Discussionmentioning
confidence: 99%